A rare case of utero peritoneal fistula - Swapna, Yendru Katyayani; Yelamanchi, Savitha Dev; Talipineni, Kamalakar Naidu; Jyothsna, Polavarapu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Uterine fistulas are very rare and can be due to gynaecological surgery, trauma or infections. 17 year old unmarried girl presented with uteroperitoneal fistula, following left salpingo-oophorectomy for torsion of left adnexae done one year ago outside. She came with increasing dysmenorrhea since surgery. USG & MRI showed cystic mass left cornual area. Vaginoscopy & Hystero-laparoscopy showed a thick longitudinal vaginal septum, uni-cornuate uterus with left horn non-communicating with cervix but open into the peritoneal cavity, the false passage being the result of previous surgery. Excision of vaginal septum and laparoscopic excision of the horn and repair provided very good relief, till now (8months from surgery).